Robust, microfabricated culture devices with improved control over the soluble microenvironment for the culture of embryonic stem cells. Issue 6 (23rd April 2014) - Macown, Rhys J.; Veraitch, Farlan S.; Szita, Nicolas
Abstract The commercial use of stem cells continues to be constrained by the difficulty and high cost of developing efficient and reliable production protocols. The use of microfabricated systems combines good control over the cellular microenvironment with reduced use of resources in process optimization. Our previously reported microfabricated culture device was shown to be suitable for the culture of embryonic stem cells but required improvements to robustness, ease of use, and dissolved gas control. In this report, we describe a number of improvements to the design of the microfabricated system to significantly improve the control over shear stress and soluble factors, particularly dissolved oxygen. These control improvements are investigated by finite element modeling. Design improvements also make the system easier to use and improve the robustness. The culture device could be applied to the optimization of pluripotent stem cell growth and differentiation, as well as the development of monitoring and control strategies and improved culture systems at various scales.